Reduction of Brain β-Amyloid (Aβ) by Fluvastatin, a Hydroxymethylglutaryl-CoA Reductase Inhibitor, through Increase in Degradation of Amyloid Precursor Protein C-terminal Fragments (APP-CTFs) and Aβ Clearance - Shinohara, Mitsuru (American Society for Biochemistry and Molecular Biology, 2010)
Epidemiological studies suggest that statins (hydroxymethylglutaryl-CoA reductase inhibitors) could reduce the risk of Alzheimer disease. Although one possible explanation is through an effect on β-amyloid (Aβ) metabolism, its effect remains to be elucidated. Here, we explored the molecular mechanisms of how statins influence Aβ metabolism. Fluvastatin at clinical doses significantly reduced Aβ and amyloid precursor protein C-terminal fragment (APP-CTF) levels among APP metabolites in the brain of C57BL/6 mice. Chronic intracerebroventricular infusion of lysosomal inhibitors blocked these effects, indicating that up-regulation of the lysosomal degradation of endogenous APP-CTFs is involved in reduced Aβ production. Biochemical analysis suggested that this was mediated by enhanced trafficking of APP-CTFs from endosomes to lysosomes, associated with marked changes of Rab proteins, which regulate endosomal function. In primary neurons, fluvastatin enhanced the degradation of APP-CTFs through an isoprenoid-dependent mechanism. Because our previous study suggests additive effects of fluvastatin on Aβ metabolism, we examined Aβ clearance rates by using the brain efflux index method and found its increased rates at high Aβ levels from brain. As LRP1 in brain microvessels was increased, up-regulation of LRP1-mediated Aβ clearance at the blood-brain barrier might be involved. In cultured brain microvessel endothelial cells, fluvastatin increased LRP1 and the uptake of Aβ, which was blocked by LRP1 antagonists, through an isoprenoid-dependent mechanism. Overall, the present study demonstrated that fluvastatin reduced Aβ level by an isoprenoid-dependent mechanism. These results have important implications for the development of disease-modifying therapy for Alzheimer disease as well as understanding of Aβ metabolism.